Early Window Tailoring: A New Approach to Increase the Number of TCP Connections Served - Marcos Talau; Mauro Fonseca; Emilio C. G. Wille (Journal of Computer Networks and Communications)
In the absence of losses, TCP constantly increases the amount of data sent per instant of time. This behavior leads to problems that affect its performance, especially when multiple devices share the same gateway. Several studies have been done to mitigate such problems, but many of them require TCP side changes or a meticulous configuration. Some studies have shown promise, such as the use of gateway techniques to change the receiver’s advertised window of ACK segments based on the amount of memory in the gateway; in this work, we use the term “network-return” to refer to these techniques. In this paper, we present a new network-return technique called early window tailoring (EWT). For its use, it does not require any modification in the TCP implementations at the sides and does not require that all routers in the path use the same congestion control mechanism, and the use in the gateway is sufficient. With the use of the simulator ns-3 and following the recommendations of RFC 7928, the new approach was tested in multiple scenarios. The EWT was compared to drop-tail, RED, ARED, and the two network-return techniques—explicit window adaptation (EWA) and active window management (AWM). In the results, it was observed that EWT was shown to be efficient in congestion control. Its use avoided losses of segments, bringing expressive gains in the transfer latency and goodput and maintaining fairness between the flows. However, unlike other approaches, the most prominent feature of EWT is its ability to maintain a very high number of active flows at a given level of segment loss rate. The EWT allowed the existence of a number of flows, which is on average 49.3% better than its best competitor and 75.8% better when no AQM scheme was used.